Pengaruh Pengetahuan dan Ketrampilan terhadap Kinerja Karyawan pada PT Bumi Mineral Sulawesi - Muhammad Kasran; Suparni Sampetan; Wilda Sanara (J-MAS (Jurnal Manajemen dan Sains), 2023)
The aim of the research is to determine the partial and simultaneous impact of knowledge and skills on the performance of employees of PT. Sulawesi Mineral Earth. The type of research used is quantitative research. The population of this research is all permanent employees of PT. Sulawesi Mineral Earth as many as 525 people. The sample acquisition method uses the Slovin formula as many as 84 respondents. The data analysis technique used is multiple linear regression. Research findings state that knowledge has a positive and significant impact on employee performance at PT. Sulawesi Mineral Earth partially. While work skills do not have an impact on the performance of employees of PT. Sulawesi Mineral Earth partially. Knowledge and skills have a positive and significant impact on the performance of employees of PT. Sulawesi Mineral Earth simultaneously, with a large influence of 34.3%, while the rest is influenced by variables that do not exist in this research of 65.7%.